Developing Digital Eco-Mathematics Teaching Materials: A Pathway to Foster Critical Thinking and Environmental Awareness - Totok Victor Didik Saputro; Silvester; Yosua Damas Sadewo; Pebria Dheni Purnasari; Falenthino Sampouw; Laurensius Robi Tarigas; Nurselam Hassen (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
The development of digital Eco-Mathematics teaching materials presents a significant opportunity to enhance elementary education by fostering critical thinking skills and environmental awareness among students. Existing mathematics learning materials rarely integrate environmental contexts in a structured and digital format, particularly in border areas, leading to limited opportunities for students to develop both competencies simultaneously. Moreover, students in border areas often experience limited access to contextual and innovative learning resources, which contributes to low levels of critical thinking skills and environmental awareness. This research aims to develop and evaluate these materials for fifth-grade students in elementary schools located in the Indonesia–Malaysia border area. Utilizing the Tesser & Akker framework, the study employs a design research approach consisting of a Preliminary Study and a Formative Evaluation to guide the development process. The analysis focuses on the validity, practicality, and effectiveness of the teaching materials in terms of educational outcomes. The findings indicate that the developed Eco-Mathematics materials meet the criteria for validity, practicality, and effectiveness. These results highlight the contribution of this study in providing an innovative integration of environmental contexts into digital mathematics learning, which effectively supports the enhancement of students’ critical thinking skills and environmental awareness, particularly in under-resourced border areas